2022
DOI: 10.1101/2022.12.13.520317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Merging short and stranded long reads improves transcript assembly

Abstract: Long-read RNA sequencing has arisen as a counterpart to short-read sequencing, with the potential to capture full-length isoforms, albeit at the cost of lower depth. Yet this potential is not fully realized due to inherent limitations of current long-read assembly methods and underdeveloped approaches to integrate short-read data. Here, we critically compare the existing methods and develop a new integrative approach to characterize a particularly challenging pool of low-abundance long noncoding RNA (lncRNA) t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
0
0
0
Order By: Relevance
“…Emerging studies have shown that hybrid transcriptome assembly approaches, which integrate short-and long-read RNAseq data, are more accurate than approaches that use data from either method independently 11,12,13,14,15,16 . Considering that the average human transcript length is one kilobase (kb) 17 and that long-read sequences are on average 1-3 kb in length 18,19 , long reads should capture the majority of human transcripts within a single read and ideally bypass the need for reassembly.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have shown that hybrid transcriptome assembly approaches, which integrate short-and long-read RNAseq data, are more accurate than approaches that use data from either method independently 11,12,13,14,15,16 . Considering that the average human transcript length is one kilobase (kb) 17 and that long-read sequences are on average 1-3 kb in length 18,19 , long reads should capture the majority of human transcripts within a single read and ideally bypass the need for reassembly.…”
Section: Introductionmentioning
confidence: 99%